Determinants of Quality of Life of Cancer Patients Undergoing Chemotherapy at Dharmais Cancer Hospital Jakarta in 2024 - -, Saman -; Ulfa, Laila; Sulistyowati, Yeny; Buwana, Cahya (http://dharmais.co.id/, 2025)
Background: Cancer is one of the non-communicable diseases that is a serious problem in health and one of the leading causes of death in the world. GLOBOCAN data shows new cases of cancer in Indonesia as many as 408,661 cases, with deaths amounting to 242,988 people. Cancer treatment, which is chemotherapy and its impact on it, can affect the patient’s quality of life. This study aims to investigate the factors that influence the quality of life of cancer patients undergoing chemotherapy at Dharmais Cancer Hospital in Jakarta. Method: Analytic observational research method with a cross-sectional design. The research was conducted in May 2024 in the inpatient room. The research sample consisted of 90 respondents using an accidental sampling technique. Data was collected on the quality of life in cancer patients undergoing chemotherapy using the European Organisation for Research and Treatment of Cancer, Quality of Life Questionnaire C30 (EORTC QLQ-C30) questionnaire instrument, which contains 30 questions about the global health scale, functional scale, and symptom scale. Data analysis in this research included univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis with multiple logistic regression test, and data processing using SPSS 25.Results: The results showed that global health status was 50% good, the functional scale was 63.3% good, the symptom scale was 55.6% good, and the patient’s quality of life was 55.6% good. Variables associated with the quality of life of cancer patients undergoing chemotherapy are nutritional status (p = 0.035) and chemotherapy education (p = 0.037). The variables of age (p = 0.178), cancer stage (p = 1.000), length of chemotherapy (p = 0.395), and family support (p = 1.000) were not significantly associated.Conclusion: Nutritional status is the most associated variable with the quality of life of cancer patients undergoing chemotherapy. It is recommended that this research be carried out, including all factors that can affect the quality of life of cancer patients undergoing chemotherapy, and evaluate changes in quality of life in each chemotherapy cycle.